How does the ground reaction force affect the 6 second sprint performance? - Baris Gurol; İlker Yılmaz; İzzet Kırkaya (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to determine kinetics and kinematics of various 6 second sprinting load with %0GRF, %10GRF and %15GRF. Different loads of GRF have been analysed for seeing effect of the increasing ground reaction force. 8 female sportswomen (age=24.7±6.2year; body weight=61.27±8.79kg; height=172.4±11.37m) of Anadolu University Youth and Sport Club that competes in the second division of Turkey Women’s Basketball participated in this study. 6s. sprint kinematical analysis of the participants was made with two fast filming cameras (A602f, Basler, Germany) that are able to record up to 500 Hz and a software program (SIMI 7.3, Germany) that is able to record the scenes simultaneously into computer in 60 Hz. The sprints that is with %0, %10 and %15 loads were applied on non-motorised treadmills during 6s., it was recorded with avi. format and the scenes which are in equal length and simultaneous were analysed. The difference among three different measurements (0%, 10%, 15% ground reaction force) that belongs to one group was tested with One Way Anova after homogeneity of variances and significance level was taken as p lt;0.05.  In the 6second sprint tests that were done with %0, %10, %15 ground reaction force, a statistically, on highest degree significant result was found among the distance that was passed, average velocity, average horizontal force, the top velocity and the top horizontal force (p≤0.01). A statistically significant relationship was not found between average vertical force and vertical force on the peak velocity (p gt;0.05).  In the 6second sprint tests which was done with 0%, 10%, 15% GRF of knee and elbow joints, statistically significant relation was not able to be found among angle, angular velocity, vertical velocity, horizontal velocity and resultant velocity (p gt;0.05). Based on Bonferroni correction post test results there were statistically significant differences have been found between ground reaction forces (GRF0 - GRF10; p lt;0.05 amp; GRF0 - GRF15; p lt;0.001) and there were no statistically significant differences have been found between ground reaction forces (p gt;0.05). During the 6second sprints that were done with 0%, 10%, 15%  of the participants’ body weights, it has been seen that vertical ground reaction force did not increase. This also shows that the participants could apply more force to the ground to accelerate and accordingly they carried out the sprint performance in a longer time. Not to be found a significant relationship among angle, angular velocity, horizontal velocity, vertical velocity and resultant velocity arises from reacting to ground reaction force in the same way with the sprint that is done with body weight. The participants could not increase their velocity in the face of increasing ground reaction force and therefore realized the 6second sprint performance in a longer time. Consequently, it has been deduced that they could not adapt acutely to ground reaction force and change their sprint styles to accelerate. To overcome the braking components of ground reaction force, supramaximal and plyometric types of trainings can be suggested.